Effects of spray-dried porcine plasma in the high nutrient density diet - L J Kats; K G Friesen; J A Hansen; Robert D Goodband; Jim L Nelssen; Michael D Tokach; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1992)
A total of 740 weanling pigs was used in three separate experiments to evaluate the effects of additions of spray-dried porcine plasma in the HNDD starter diet. In Trial 1, 534 weanling pigs (initially 14.1 lb and 21 d of age) were used to evaluate various levels of spray-dried porcine plasma. Pigs were assigned to one of six experimental diets with either 0, 2, 4, 6, 8, or 10% spray-dried porcine plasma replacing dried skim milk. Pigs were fed this diet for the first 14 days postweaning, when they were switched to a common phase II diet (d 14 to 28). During phase I (d 0 to 14), linearÂ· and quadratic improvements occurred in average daily gain and average daily feed intake. No significant differences occurred in feed efficiency for any phase of the eXPeriment. In Trial 2, 68 weanling pigs (12.7 lb and 21 d of age) were used to determine if supplemental methionine is needed for diets containing high levels of spray-dried porcine plasma. Pigs were fed identical diets containing 20% dried whey, 7.5%spray-dried porcine plasma, and 1.75% spray-dried blood meal except that one diet contained 2 lblton supplemental DL-methionine. Pigs receiving diets containing supplemental methionine had improved average daily gain and average daily feed intake during the first week postweaning. Feed efficiency also was improved for the overall trial. In Trial 3, 144 weanling pigs (initially 12.61b and 19 d of age) were used in a 21-d growth trial to evaluate two different sources of spray-dried porcine plasma. Pigs were assigned one of two diets containing 20% dried whey and 10% spray-dried porcine plasma. Pigs receiving the diet containing spray-dried porcine plasma obtained from source 1 had improved average daily gain for all phases of the eXPeriment and increased average daily feed intake for d 0 to 14 and d 0 to 21 compared to pigs fed the diet containing spraydried porcine plasma from source 2. There were no differences in feed efficiency. In conclusion, these trials demonstrate three key points concerning spray-dried porcine plasma: 1) starter pig performance is improved linearly with increasing levels of spray-dried porcine plasma through 10% of the diet; 2) DL-methionine must be added to diets containing high levels of spray-dried porcine plasma to obtain optimal performance; and 3) there are differences in commercially available sources of spray-dried porcine plasma.; Swine Day, Manhattan, KS, November 19, 1992
Keywords: Swine day; 1992; Kansas Agricultural Experiment Station contribution; no. 93-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 667; Swine; Starter; Spray-dried porcine plasma; Performance